Usigli’s Medio tono and the Transition to Modern Mexican Theatre - Cohen, Deb (Latin American Theatre Review, 2001)
Many (including the author himself) consider Rodolfo Usigli to be the father of modern Mexican theatre. In particular, Ramón Layera and others often point to El gesticulador as the play that marks the transition from colonial theatrical practices to modern ones. This article proposes Medio tono as the play that definitively breaks from previous theatrical traditions through its use of a large ensemble cast, quick dialogue turnover, simultaneous dialogue, and other factors that would be difficult to achieve under the old system of one week for rehearsals, a plush role for the star/director, and reliance on a prompter. (DC)